Systemowe metody monitorowania jakości pracy w urzędach administracji publicznej - Walenia, Alina (Annales. Etyka w Życiu Gospodarczym, 2020)
Implementing modern methods of quality management improves the services provided by public administration. Quality management systems are tools for changing the structure, methods of operation, and consequently, the image of Polish administration. These systems are a modern method aimed at improving the management and quality of the public services provided. Implementing the system of solutions based on the ISO 9001 standard that ensures quality requires customers’ needs to continually be improved, defined and fulfilled effectively and economically. Such activities in public administration offices make it possible to develop transparent, ordered, self-improving organisations that are open to customers’ and employees’ needs. The system of quality management ensures the functioning of offices in accordance with the rules of law, objectivity, and professional ethics. The purpose of this article is to assess the impact of systems methods of quality management in the public sector on the effectiveness and efficiency of the services provided, including the principles of professional ethics.